Semiotics of the Saudi heritage in the light of contemporary technology - Abjabal, Manal Eid Sanusi; Fayoumi, Foton Fouad Abdulkadir (Arab Journal for Sciences and Research Publishing, 2023)
The research aimed to take advantage of digital technology in showing the semiotics of the Saudi heritage in a contemporary form, based on revealing the connotations and semiotics of the Najdi decorations in the Kingdom of Saudi Arabia, the central region (Najd). These motifs express it. The research used the descriptive and analytical method to identify the patterns of Najdi motifs, and the most important symbolic indications that these motifs express. The research reached a set of results, including that the Saudi artist excelled in using various types of decorative symbols, whether geometric, plant or natural, in his decorations on the traditional architecture of Najd, and that the Najdi artist was affected by his environment in which he lived, and this was evident in his decorations on the architecture. He used the sun, stars and moon, those things that affected him and his life, as the sun and stars are among the most important environmental influences that had a great significance in his decorations. He also used geometric symbols such as triangles, squares, and circles, and these had great significance in the life of a person in Najd, as each geometric symbol symbolized a specific thing in his life, or a fear of a certain thing, such as envy and others.
Keywords: Semiotics; Heritage; Contemporary